-9-23=9p-7p

Simple and best practice solution for -9-23=9p-7p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9-23=9p-7p equation:



-9-23=9p-7p
We move all terms to the left:
-9-23-(9p-7p)=0
We add all the numbers together, and all the variables
-(+2p)-9-23=0
We add all the numbers together, and all the variables
-(+2p)-32=0
We get rid of parentheses
-2p-32=0
We move all terms containing p to the left, all other terms to the right
-2p=32
p=32/-2
p=-16

See similar equations:

| -2x-5+3x=2 | | -k+6(k+1)=4k | | 72/n=80 | | 4p-8(-4-8p)=508 | | 3x+2+127=180 | | -1x+(3-x)=2x-7 | | 2/3x+1/4x=2 | | 5m/8-6/8+3m/8=@/8 | | 3/4=x-3/8 | | 4.5(x-9)=2.96 | | 7x=x-870 | | 6x-37+8x-99=180 | | -9.04-3(0.2q-1)=-18.28 | | 3+2x+-1x+-1=3x+-6 | | 1.5^x=3.72 | | –1.6p=8 | | 4x+3.4=9.1 | | 1/4x+5/12x=4 | | 5x+24=2x-9-3x | | 3/4x+5=1/2x+15 | | 0.08(y-3)+0.16y=0.04y-0.5 | | 7×3x=23 | | –1.6x=8 | | 6x+11=10x-25 | | 3h+1=5.50 | | -3w^2+10w+8=0 | | 3h-1=5.50 | | x+6(x-1)=7(+x) | | 2/7x-2=9/7x | | -1+b/3=5 | | 1/4w-4/3=-4/5 | | 6x-8-2x=-18 |

Equations solver categories